2011
DOI: 10.1007/dcr.0b013e318216067d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery Versus Conventional Perioperative Care in Rectal Surgery

Abstract: Enhanced recovery after surgery programs help to reduce the length of hospital stay after rectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 26 publications
3
11
0
2
Order By: Relevance
“…rectal cancer surgery is known to be associated with higher complication rates and longer hospital stay than is colon resection. However, a reduction in the length of stay was found in patients who underwent laparoscopic rectal resection in this study when compared with 8-10 days in other studies (26,27), although shorter hospitalization time has also been reported (28). our results are in keeping with Delaney et al (29), who reported a reduced length of stay among patients who underwent complex pelvic and abdominal procedures such as total proctocolectomies and abdominoperineal resections in the fast-track setting.…”
Section: Determinants Affecting Postoperative Hospital Staysupporting
confidence: 88%
“…rectal cancer surgery is known to be associated with higher complication rates and longer hospital stay than is colon resection. However, a reduction in the length of stay was found in patients who underwent laparoscopic rectal resection in this study when compared with 8-10 days in other studies (26,27), although shorter hospitalization time has also been reported (28). our results are in keeping with Delaney et al (29), who reported a reduced length of stay among patients who underwent complex pelvic and abdominal procedures such as total proctocolectomies and abdominoperineal resections in the fast-track setting.…”
Section: Determinants Affecting Postoperative Hospital Staysupporting
confidence: 88%
“…Teeuwan et al [31], in a study focused on rectal surgery patients, noticed a trend towards an increased readmission rate in the ERAS group, although the difference was not significant. This raises the question if early discharge is likely to raise readmission rates.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, two cohort studies comparing ERAS and conventional perioperative care reported similar results: Teeuwen et al [31] studied results in open rectal surgery, and Huibers et al [32] in laparoscopic total mesorectal excision for rectal cancer. Both studies showed significantly shorter LOSH in the ERAS group [(median: 8 days vs. 12 days, p<0.005) and (median: 7 days vs. 10 days, p<0.001), respectively], with no significant difference in mortality, morbidity, and readmission rates between groups.…”
Section: Rectal Surgerymentioning
confidence: 86%
See 2 more Smart Citations